Influence of native and exotic plant diet on the gut microbiome of the Gray's Malayan stick insect, Lonchodes brevipes - Lim, Yan Zhen; Poh, Yan Hong; Lee, Kevin C.; Pointing, Stephen Brian; Wainwright, Benjamin J.; Tan, Eunice Jingmei (Frontiers in Microbiology, 2023)
Herbivorous insects require an active lignocellulolytic microbiome to process their diet. Stick insects (phasmids) are common in the tropics and display a cosmopolitan host plant feeding preference. The microbiomes of social insects are vertically transmitted to offspring, whilst for solitary species such as phasmids, it has been assumed that microbiomes are acquired from their diet. This study reports characterization of the gut microbiome for the Gray’s Malayan stick insect, Lonchodes brevipes, reared on native and introduced species of host plants and compared to the microbiome of the host plant and surrounding soil to gain insight on possible sources of recruitment. Clear differences in gut microbiome occurred between insects fed on native and exotic plant diets, and the native diet displayed a more species-rich fungal microbiome. Whilst the findings suggest that phasmids may be capable of adapting their gut microbiome to changing diet, it is uncertain whether this may lead to any change in dietary efficiency or organismal fitness. Further insight in this regard may assist conservation and management decision-making.